Radiologic Assessment of the Paranasal Sinuses after Endoscopic Skull Base Surgery - DeConde, Adam S.; Vira, Darshni; Thompson, Christopher F.; Wang, Marilene B.; Bergsneider, Marvin; Suh, Jeffrey D. (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objectives To identify sinuses demonstrating postoperative radiographic mucosal thickening after endoscopic exposure of the cranial base through the transsphenoidal corridor.Design Retrospective review.Setting University-based medical center.Participants Patients undergoing endoscopic transnasal transsphenoidal approaches to the skull base who had both preoperative and postoperative imaging.Main Outcome Measures Change in preoperative and postoperative imaging scores for each sinus and side at 3 and 6 months. The left-sided undissected sinuses served as internal controls for comparison.Results Fifty-one patients were identified with the aforementioned inclusion and exclusion criteria. The mean difference in preoperative and postoperative imaging scores for the right anterior ethmoid sinus was significantly different from the left-sided equivalents (p = 0.0020). The difference in the frontal sinuses approached significance (p = 0.0625).Conclusions Resection of the lower half of the middle turbinate and maxillary antrostomy and harvest of a nasoseptal flap are associated with an increased radiographic incidence of mucosal thickening of the ipsilateral anterior ethmoids compared with the undissected contralateral side. When accessing the transnasal transsphenoidal corridor for skull base surgery, preservation of native anatomy is associated with a lower incidence of mucosal thickening on postoperative imaging.
Keywords: endoscopic skull base; middle turbinate; sinusitis; maxillary sinus; radiographic